IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH IDIOMATIC EXPRESSION IN COMIC STRIPS - Sitty Sulastri Waliulu; Muhammad Chairil Imran; Sulviana Sulviana (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2024)
The objective of this research was to determine whether the use of idiomatic expressions in comic strips increased the mastery in eighth class of SMP Negeri 11 Huamual and to determine whether the used of idiomatic expressions in comic strips increased the motivation in eighth class of SMP Negeri 11 Huamual. This research used a quasi-experimental design involving two class groups. The population of this research used in eighth class students of SMP Negeri 11 Huamual which found 56 students. The sample of this research used students of class VIIIA which consisted of 28 students as the experimental class and 28 students of class VIIIB as the control class. The research instrument is a vocabulary test and questionnaire. The results of the research on the vocabulary test showed that there was a significant difference between the post-test of the experimental class and the control class. The average post-test value of the experimental class is 75.21, greater than the post-test value of the control class, which is 67.35, meaning that the average value obtained is a good qualification. Students' interest in understanding vocabulary increased through idiomatic expressions in comic strips using a Likert Scale.